PENINGKATAN KEMAMPUAN PENILAIAN PEMBELAJARAN GEOGRAFI - Mukminan, Mukminan; Suparmini, Suparmini; Nursa'ban, Muhammad (Universitas Negeri Yogyakarta, 2013)
The results of policy research in 2009 showed that geography teachers' understanding and skills in learning assessment still have not reached the standard. The purpose of this activity is the increased understanding of assessment techniques by geography teachers in Bantul with indicators of success at least 70% of participants obtain the results of the assessment in the category ofat least